EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DAN PROBLEM POSING BENTUK WITHIN-SOLUTION POSING PADA MATERI PERBANDINGAN DITINJAU DARI KECERDASAN INTERPERSONAL SISWA SMP NEGERI KOTA PONTIANAK - Susiaty, Utin Desy; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aims of this study were to investigate: (1) which learning model produces studentâs better mathematics learning achievement, Cooperative Integrated Reading and Composition (CIRC), Problem Posing Learning Model Within-Solution Posing (WSP) Form or classical learning model; (2) which studentâs have better mathematics learning achievement, those with high, medium, or low interpersonal intelligence; (3) viewed from learning models, which studentâs have better mathematics learning achievement, those with high, medium, or low interpersonal intelligence; (4) viewed from interpersonal intelligences, which learning model produces better mathematics learning achievement, CIRC, WSP or classical learning model. This research used quasi experimental method with its population included all of students of state junior high school in Pontianak City. Sampling was done by stratified cluster random sampling technique. The size of the sample was 313 students. The data collection technique was include the documentation method to get the 2013/2014 National Test (UN) of Elementary School for initial capability data before the experiment, achievement test for mathematics studentâs achievement data, and questioner of interpersonal intelligence. The data was analyzed using analysis of variance. Based on these results it can be concluded as follows. (1) Mathematics learning using CIRC produced the same mathematics achievement as using classical learning model. However, mathematics learning using WSP produced studentâs better mathematics learning achievement than using CIRC and classical learning model. (2) For students with high, medium, or low interpersonal intelligence have the same mathematics achievement. (3) Viewed from learning models, students with high, medium, or low interpersonal intelligence have the same mathematics achievement. (4) Viewed from interpersonal intelligences, mathematics learning using WSP produced studentâs better mathematics learning achievement than using CIRC and classical learning model. However, mathematics learning using CIRC and classical learning model have the same mathematics achievement.Keywords: CIRC learning model, WSP learning model, interpersonal intelligence, the mathematical achievement